A 2 year retrospective evaluation of mannheim peritonitis index in patients with secondary peritonitis in Hospital Universiti Sains Malaysia (from January 2013 to October 2014) - A/L Balasubbiah, Narendran (2015)
Topic: A 2 year retrospective evaluation of Mannheim peritonitis index in patients with secondary peritonitis in Hospital Universiti Sains Malaysia (January 2013 - October 2014). Backgound: For decades, peritonitis has presented surgeons a challenge despite newer advances in various facets of medicine. The risk stratification of patients is important to appropriately study the individual risk factors to predict possible outcome in terms of morbidity and mortality. The objective of this study is to evaluate the Mannheim peritonitis index in determining the outcome in patients operated for secondary peritonitis in HUSM. Method: The study population consisted of patients who underwent any form of intra-abdominal operations for secondary peritonitis during the period of study. The total number of patients were 113. The patient’s medical records was traced from the hospital records department after permission was granted from the Hospital Director. The relevant socio demographic, clinical, operative notes and survival status was entered into a proforma form. All the data recorded was entered into SPSS software version 21 and analyzed. Pearson chi-square and independent t-test were used as statistical tests . Significant difference was taken into account if the probability or ‘p’ value is equal or less than 0.05. Results: The mean MPI score was 25.22 (+- 8.03) with the lowest score of 10 and highest score of 43. The threshold MPI score was 26.5 and there was only 1 death which occurred below this score. No deaths occurred below score of 21. The significant predictive factors for mortality was age more than 50 years, gender, organ failure and diffuse generalized peritonitis. Meanwhile, all parameters for MPI affected the MPI scoring except for source of sepsis not from colon. The ROC curve for mortality showed a sensitivity of 94.7% and specificity of 70.2% at a threshold MPI of 26.5. Conclusion: For patients with secondary peritonitis undergoing operation, MPI scoring would be the best for grading severity and prognosis due to its simplicity and cost efficiency. Further increase in its prognostic power is desirable with some physiological data such as from APACHE 2. Application of MPI in the Malaysian population would be appropriate by changing the source of sepsis parameter to a higher score for those who have colonic source instead of non colonic which is the current MPI scoring system.